Computed Tomography-Assessed Sarcopenia Predicts Mortality in Kidney Transplant Candidates - KURŞUN, MELTEM; ÇİMŞİT, CANAN (My University, 2024)
Objectives: Sarcopenia is common in chronic kidney disease and associated with increased mortality. We investigated the prevalence of sarcopenia, defined as low muscle mass by the psoas muscle index, in end-stage renal disease patients on waiting lists for kidney transplant and determined its association with prognostic nutritional index, C-reactive protein-to-albumin ratio, cardiovascular events, and mortality. Materials and Methods: Our study included 162 patients with end-stage renal disease and 87 age-matched healthy controls. We calculated nutritional status as follows: prognostic nutritional index = (10 × albumin [g/dL]) + (0.005 × total lymphocyte count (×103/μL]) and C-reactive protein-to-albumin ratio. We gathered demographic and laboratory data from medical records. Results: Patients with end-stage renal disease had a mean age of 44.7 ± 14.2 years; follow-up time was 3.37 years (range, 0.35-9.60 y). Although patients with end-stage renal disease versus controls had higher prevalence of sarcopenia (16.7% vs 3.4%; P =.002) and C-reactive protein-to-albumin ratio (1.47 [range, 0.12-37.10] vs 0.74 [range, 0.21-10.20]; P <.001), prognostic nutritional index was lower (40 [range, 20.4-52.2] vs 44 [range, 36.1-53.0]; P <.001). In patients with end-stage renal disease with and without sarcopenia, prognostic nutritional index (P =.005) was lower and C-reactive protein-to-albumin ratio (P =.041) was higher in those with versus those without sarcopenia. Among 67 patients on waiting lists who received kidney transplants, those without sarcopenia had better 5-year patient survival posttransplant than those with sarcopenia (P =.001). Multivariate regression analysis showed sarcopenia and low prognostic nutritional index were independent risk factors for mortality among patients with end-stage renal disease. Conclusions: Sarcopenia was ~5 times more frequent in patients with end-stage renal disease than in healthy controls and was positively correlated with the prognostic nutritional index. Sarcopenia was an independent risk factor for mortality in patients on transplant waiting lists.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; TRANSPLANTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; TRANSPLANTATION; Transplantasyon; Transplantation; C-reactive protein-to-albumin ratio; Prognostic nutritional index; Psoas muscle index; Renal transplantation